Les privatisations en Turquie : un regard critique - Tugen, Kamil; Gunay Bekar, Ayse; Koymen, Sebnem (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The meaning of privatisation is to minimize the role of government in the economy and to assign these roles to the private sector. The economic and social problems caused by the excess role of government in the economy led a heated debate on the limits of government throughout the world at the end of the 20th century. In this respect, significant research have been put forward on the preference of the timing of government intervention and market intervention. In the suggestions about the reduction of the role of government in the economy, privatisation has gained importance but the implementations on privatisation have sometimes been criticized because of not having been implemented according to the principles and aims of privatisation. In this regard, the privatisation in the Turkish economy has often been criticized
Keywords: przedsiębiorstwa gospodarcze; prywatyzacja; deregulacja; regulacje; kapitał zagraniczny